2021
DOI: 10.1111/jsap.13317
|View full text |Cite
|
Sign up to set email alerts
|

Migrating grass awn within the intraconal part of the retrobulbar space in a dog

Abstract: A 1.5-year-old MC Cardigan Welsh Corgi was presented for a right oral fistula associated with left tonsil enlargement that responded to medical treatment. A first computed tomography scan was performed and showed no signs of a foreign body. Medical treatment was continued for 2 additional weeks and the dog was free of clinical signs for 3 months. The dog was presented again for a 3-day history of anorexia and marked pain when opening the jaw. The repeat computed tomography scan revealed a migrating foreign bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Similarly, in another case report, ultrasonography was used to drain an abscess in the left medial temporalis muscle of a dog, but the grass awn was not visualized [ 39 ]. In two recent case reports, ocular and orbital US failed to identify the presence of grass awns in the conjunctivoscleral region [ 40 ] and in the intraconal part of the retrobulbar space [ 41 ]. In contrast with these findings, several studies demonstrated the utility of ultrasonography in diagnosing ocular foreign bodies [ 38 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in another case report, ultrasonography was used to drain an abscess in the left medial temporalis muscle of a dog, but the grass awn was not visualized [ 39 ]. In two recent case reports, ocular and orbital US failed to identify the presence of grass awns in the conjunctivoscleral region [ 40 ] and in the intraconal part of the retrobulbar space [ 41 ]. In contrast with these findings, several studies demonstrated the utility of ultrasonography in diagnosing ocular foreign bodies [ 38 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%